“Risks”, “harm” and “benefits” of participating in a COVID-19 oral history project (Práxis Educativa, 2023)
Empirically based on a set of oral history interviews in the project Documenting the COVID-19 experience in Rio Grande do Sul, this text presents and questions the notions of “risks”, “harm” and “benefits” associated with participation in research and tributaries of bioethics and institutional evaluation of projects in the Health area. At the same time, and based on oral history literature, it demonstrates how they can be useful in everyday research practice. The reflections developed in the research project “Oral History and Public History: dialogues, challenges and possibilities – a comparative look between Brazil, Italy and Canada” and the involvement in Working Groups on ethics in the Brazilian Association of Oral History (ABHO) and in the Human, Social, Applied Social Sciences, Linguistics, Language and Arts Forum (FCHSSALLA) contribute to the development of the theme. The text is organized in four parts: in the first, institutional norms for evaluating ethics are presented, with regard to “risks”, “harm” and “benefits” associated with participation in “research with human beings”; in the second, the literature on ethics, collaborative work and good practices in oral history is explored; in the last two parts, a dialogue is developed with a set of interviews given by the Universidade Federal do Rio Grande do Sul (UFRGS) undergraduate students with a low-income profile. At that moment, the aforementioned notions and the precautions adopted by the research team are located in the oral sources.Keywords: Ethics. Oral history. Covid-19.